Cyclic simple shear behavior of a tropical alluvial soil - Alsidqi, Hasan; Nisa, Ismail; Yieng, Yung Chuo; Lin, Jye Lee (Elsevier Science, Ltd., 2023)
Tropical alluvial soil has distinctive physical characteristics when compared to common sedimentary soils. Ignoring such distinctive characteristics might lead to geotechnical problems that require a thorough reinvestigation. Foundation failures have been identified along some river banks of tropical alluvial soil deposits in Sarawak, Malaysia, which were speculated to be due to cyclic loading effects. This paper presents preliminary results on tropical alluvial soil engineering behaviors from simple shear cyclic loading tests. Specimens measuring 50 mm in diameter and 16 mm in height were obtained from three undisturbed samples. They were sheared using an Electro-Mechanical Dynamic Cyclic Simple Shear (EMDCSS) for thirty cycles at three different target displacements. The results showed hysteresis loops, where the shear stress decreases as the cycle increases. Excess pore water pressures develop during shearing, which correspond to the target displacement levels. The damping ratio increases as the shear strain increases but decreases as the cycle increases. The normalized shear modulus decreases as both the shear strain and loading cycle increase. A comparison with previous literature on cohesive soils shows that the tropical alluvial soil has a lower damping ratio and normalized shear modulus, which range from 3.3% to 9% and 0.0004 to 0.01, respectively. The findings indicate that the tropical alluvial soil has a potential reduction in strength when subjected to continuous cyclic loading. The paper provides a better understanding for academics and engineering professionals before conducting design or remedial work in the tropical alluvial soil environment.